2022
DOI: 10.3389/fenvs.2022.858816
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation of Soil Phosphorus and Its Implications for Future Pomelo Orcharding System Management: A Model Prediction From Southeast China From 1985–2100

Abstract: Phosphorus (P) is a non-renewable source, requires in large amount for maintaining better crop growth and development. The excessive P fertilizer contributes to the accumulation of P in the soil and results in increased soil total P and Olsen P. However, the spatio-temporal variation of soil P remains unclear in pomelo orchard systems. Therefore, this study aimed to assess the temporal and spatial variation of soil P in pomelo orchards and future to predict P pool from 1985 to 2100, based on the dynamic P pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Proteobacteria was positively correlated with AP, AK, and AN because it is categorized into a copiotroph group that prefers high-nutrient soil resources (Eilers et al, 2010). Acidobacteria was positively correlated with soil pH and consistent with previous findings (Wang et al, 2018;Muneer et al, 2022). Various studies have reported inconsistent results of soil pH on Acidobacteria, where some studies also have shown a negative correlation (Jones et al, 2009;Navarrete et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Proteobacteria was positively correlated with AP, AK, and AN because it is categorized into a copiotroph group that prefers high-nutrient soil resources (Eilers et al, 2010). Acidobacteria was positively correlated with soil pH and consistent with previous findings (Wang et al, 2018;Muneer et al, 2022). Various studies have reported inconsistent results of soil pH on Acidobacteria, where some studies also have shown a negative correlation (Jones et al, 2009;Navarrete et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…At the final stage, hydrolyzed-N was titrated with H 2 SO 4 (Zhou et al, 2022). Available phosphorous (AP) was extracted using 0.5 mol L −1 of sodium bicarbonate (NaHCO 3 ) at pH 8.5 and quantified by a SpectraMax M4 spectrophotometer (Molecular Devices, Ca, USA) (Yan et al, 2022). Available potassium (AK) was extracted with ammonium acetate solution (NH 4 CH 3 CO 2 ) and quantified by flame photometry (FP6410, INESA, China) (Guo et al, 2022).…”
Section: Determination Of Soil Physicochemical Propertiesmentioning
confidence: 99%
“…A further key element for plant nutrition is P, which is responsible for plant growth, reproduction and energy transfer within the plant. In agriculture, mineral P is used as fertilizer but P reservoirs are limited and depleting (Sulieman & Mühling, 2021; Yan et al, 2022). Therefore, P cycling gains a rising interest in agricultural praxis.…”
Section: Introductionmentioning
confidence: 99%
“…The soil is basically considered acidic with poor soil fertility ( Chen et al, 2022 ). To improve pomelo fruits yield, farmers use excessive use of chemical fertilizers, including nitrogen, phosphorus, and potassium ( Yan et al, 2022 ), which results in soil acidification, destroying soil structure, reducing soil organic matter, and inhibiting the absorption of soil nutrients ( Iqbal et al, 2021 ; Ali et al, 2022 ). Soil nutrient status is the most critical factor which affects soil microbes ( Paul, 2014 ).…”
Section: Introductionmentioning
confidence: 99%